Foreign Workers in Indonesia: A Literature Study of The Islamic Perspective - Andrean, Rizky; Safi'i, M. Aris; Surur, Achmad Tubagus (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2023)
This study aims to describe foreign workers in Indonesia from an Islamic perspective. This research is a literature study using a qualitative research approach. This research uses secondary data that comes from the publication of scientific journal articles, the results of previous studies, and other reference sources that are relevant to the matter being studied. The development of globalization encourages the movement of labor between countries, giving rise to foreign workers. Foreign workers are every person who is not an Indonesian citizen who can do work, both inside and outside the employment relationship, to produce goods or services to meet the needs of society. Foreign workers can have positive and negative impacts on domestic employment conditions. Therefore, the government needs to make regulations regarding foreign workers. The policies issued by the government to regulate foreign workers in Indonesia must be fair. Labor from an Islamic perspective is a partner towards achieving common prosperity that must be treated humanely, including if the workforce is foreign workers. From an Islamic perspective, foreign workers should be respected according to their proportions based on general rules and norms that apply. The existence of foreign workers should be a momentum to advance the nation’s economy.